Photosynthetic response and agronomic performance of maize intercropped with beans using different planting patterns and fertilizers under the ambient conditions of the Colombian Amazon - Suárez, Juan Carlos; Anzola, José Alexander; Vanegas, Jose Ivan; Salas, Dina Luz; Contreras, Amara Tatiana; Idupulapati, Rao (2025)
Small holders in the Colombian Amazon region use maize-bean intercropping for improving productivity under the combined stress conditions of acidic soils and high temperature. This study is aimed to evaluate the photosynthetic response and agronomic performance of maize (Zea mays L.) variety (ICA V109) intercropped with two improved lines of common bean (BFS 10, ALB 121) with three different planting patterns (Monocropping pattern (MCP); Intercropping pattern 1:1 (ICP 1:1); Intercropping pattern 2:1 (ICP 2:1)) and two types of fertilizer application (Nutrimins Inorganic Fertilizer (NIF); Super Magro Biofertilizer (SMB)) under the field conditions of the Colombian Amazon. Photosynthetic response and agronomic performance of maize plants were evaluated at different phenological stages over two seasons. The functioning of the photosynthetic apparatus was evaluated by means of parameters derived from light and CO2 response curves, as well as the level of stress tolerance in terms of chlorophyll a fluorescence. Agronomic performance was evaluated based on grain yield and yield components. Maximum rate of carbon fixation (Amax) was higher with the SMB compared to the NIF application for the MCP and the ICP 1:1, however in the ICP 2:1 it was higher with the SMB application. For photosynthetic parameters such as the maximum carboxylation rate (Vcmax) and the maximum rate of electron transport driving regeneration of ribulose-1,5-bisphosphate (Jmax) were higher with the ICP 2:1. These results indicate that microclimatic conditions under intercropping allowed greater gas exchange compared to monocropping pattern and improved photosynthetic rates and increased crop yields. Based on photosynthetic response and agronomic performance, we recommend the use of maize variety ICA V109 planted as an intercrop with common bean using an ICP 1:1 with the application of SMB under the ambient conditions of the Colombian Amazon region.